Responsibility of the administrators of the cooperative societies in a situation of forced dissolution - Huerta Viesca, María Isabel; Rodríguez Ruiz de Villa, Daniel (Cooperativismo & Desarrollo, 2019)
This article presents the analysis and systematization of the Spanish regional legislation concerning liability of managers of cooperative societies when cases of forced dissolution. Similarly, a study of State Laws on the issue. A proposal for harmonization and improvement of regional and State Laws to ensure a uniform legal regime applicable also to European cooperative Society domiciled anywhere in Spain.